The Role of School Leadership in Improving Teacher Motivation and Student Performance in Penajam - Handayani, Fransisca Heny; Sarinah, Syifa; Inayah, Inayah (Educia Journal, 2023)
This is a qualitative research study seeking to determine how leadership in schools can help in motivating teachers as well as improve on students’ performance. A prospective quantitative study is carried out in Penajam to compare the two research questions on how participatory and transformational leadership affects teacher engagement and its relation to the students’ outcomes. Conducting interviews with the teachers, the work confirms that-being receptive and open to all, the leaders undoubtedly enhance the motivation level of teachers and as a result – the levels of classroom activity, the creativity in approaching the tasks, and the achievements of students are also raised. On the other hand, autocratic leadership and other similar leadership practices were seen to have negative impacts on the motivation of the teachers and thus the students’ performance. The study brings into focus that teacher motivation, backed up by good leadership improves school climate, reduces lumpenism and enhances academic performance. Of particular relevance in the study is the need to maintain leadership support, proper resource provision and organizational support to keep the teachers motivated as well as to support long-term students’ outcomes. The findings of this study may be useful for school leaders as well as policymakers to pay timely attention towards the necessity of better leadership approach in order to improve education.